Teacher’s Role: Learning Service of Children with Special Needs in Inclusive School - Ria Asrina Marza; Dewi Nasien; Agus Joko Purwanto (Universitas Pendidikan Ganesha, 2022)
Children with special needs require more optimal handling from teachers, but the reality in the field is that learning services for children with special needs are still not optimal. The purpose of this study was to analyze how learning services for children with disabilities through the role of teachers. The subjects in this study were teachers in inclusive school. This research is descriptive qualitative research with interview and documentation as data collection. Data analysis is carried out in 3 (three) stages there are data reduction, data coding, and data tabulation. The results showed those services for children with special needs carried out at the primary school for inclusive education organizers, the school provides services in the form of identification and assessment. Life skills development activities at the primary school organizing inclusive education are still limited to extracurricular activities, there are no special life skills development activities for children with special needs, extracurricular activities at the primary school organizing inclusive education already have several activities to develop the abilities and talents of students. Extracurricular activities are already running and are carried outside of school hours.